The effect of football matches on crime patterns in Barcelona - Simon Planells Struse; Daniel Montolio (European Regional Science Association (ERSA), 2014)
Given the actual debate, in many European countries, about the need for public administrations to raise their revenues through taxing the crime externalities generated by some private leisure activities, this article analyzes the effect of football matches on crime focusing both on property crimes and interpersonal violent crimes. Our aim is to determine up to what extent a private leisure activity, such as football matches, induces negative crime externalities to the whole society. Using data on both football matches played by Football Club Barcelona (FCB) and geocoded recorded crime data for the City of Barcelona, we firstly evaluate, by means of an Exploratory Spatial Data Analysis (ESDA) at a census tract level, the effect of the number of attendees to football matches on crime by comparing crimes occurring during home and away matches. Secondly, we focus on the effect on the spatial distribution of crime when holding football matches by means of a negative binomial regression. The results regarding property crimes indicate an increase of the number of crimes for the whole city of Barcelona and, specially, in those census tracts that are up to 1 km away from the stadium, indicating that even though there exists a large increase in the number of police officers around the stadium, potential offenders are attracted to crowds where the rewards are higher and the probability of apprehension is lower. These results are confirmed by the low number of recorded crimes on away football matches on the census tracts around the stadium. Regarding violent interpersonal crimes, we find a similar spatial pattern than for property crimes although the overall impact for the whole city is not significant. This result suggests that there exists an important displacement effect towards the census tracts close the FCB stadium.
Keywords: L31; R10; L83; 330